MINAT MAHASISWA TAMATAN IPA MASUK JURUSAN SOSIOLOGI FISIP UNIVERSITAS RIAU - Gilang Gusrianto; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in the departmental environment of Sociology Faculty of Social and Political Sciences of Riau University which aims to know the interest and obstacles of IPA graduates entering the department of Sociology FISIP UR. This research topic discusses the interests, motivation, parents, expected work, and learning environment. The informant consisted of 8 students. This research is descriptive qualitative with in-depth interview. The conclusion; 1) Student interest consists of interest, motivation, parents, expected work, and learning environment. Their perception before applying to college considers the sociology department easier than any other department. Student motivation because of the opportunity to get a job especially in the last few years is often heard CPNS job vacancy, their motivation also want to continue the education of Strata two because in Riau has many universities that have courses for the level of Strata two Fisip. Factor parents of students admitted not forced to major in sociology because it is a graduate of SBMPTN and PBUD / PBM. The work expected by the students is expects to be accepted to work in government institution become civil servant (PNS). From the environmental factors of learning, the students admitted that they believe the learning environment has been accredited. 2) Obstacles faced by students were doesn’t have a foundation of governmental science yet because in their high school majoring in science, in addition to the constraints of the lecture is the difficulty of adapting to the complex college hours.Keyword: Interest, Graduated IPA students, Sociology